THE EFFECT OF SOCIAL MEDIA MARKETING ON SALES (CASE STUDY OF WASHYOURSHOES IN MAKASSAR CITY) - Ismail Hamid; Anwar Ramli, Muhammad Ilham Wardhana Haeruddin, Tenri Sayu Puspitaningsih Dipoatmodjo, Zainal Ruma (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
This study intends to find out whether Social Media Marketing or SMM has a Significantly Positive effect on WashYourShoes Sales in the city of Makassar. Samples were taken from WYS consumer respondents in the city of Makassar with a total sample of 110 people. The method used by the researcher is the Questionnaire and Documentation. The data analysis technique used is simple regression analysis using Statistical Product and Service Solution (SPSS). The results of this study indicate that SMM (Social Media Marketing) has a significant positive effect on Sales of WYS (WashYourShoes) in Makassar City.